The Importance of Excluding Cutaneous T-Cell Lymphomas in Patients with a Working Diagnosis of Papuloerythroderma of Ofuji: A Case Series - Anthony M. Maher; Chloé E. Ward; Steven Glassman; Ivan V. Litvinov (Karger Publishers, 2018)
Papuloerythroderma of Ofuji (PEO) is an erythroderma-like eruption with flat-topped papules that spare the skin folds (a "deck-chair sign" finding). Many infections, medications, and systemic diseases have been associated with PEO, including cutaneous T-cell lymphomas (CTCL). The relationship between the clinical presentation of PEO and CTCL remains poorly elucidated. Clinical, laboratory, and histopathological data were obtained from the Lymphoma Clinic at the Ottawa Hospital, Canada. We report 5 patients with deck-chair-sign-positive CTCL, mycosis fungoides, and Sézary syndrome variants. We contend that PEO should be viewed as a diagnosis of exclusion and that these patients should be monitored carefully for possible emergence of CTCL. Skin biopsy alone is not sufficient to exclude CTCL in these patients. A skin eruption demonstrating a positive deck-chair sign may signify systemic/leukemic CTCL and, therefore, warrants a thorough investigation, including skin biopsy, flow cytometry, and T-cell receptor clonality studies.